1997
DOI: 10.3109/08860229709037218
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Specificity of Transferrin Saturation and Serum Ferritin as Markers of Iron Status After Intravenous Iron Dextran in Hemodialysis Patients

Abstract: This study was designed to investigate the effect of intravenous (i.v.) iron dextran (ID) on hematocrit (Hct), transferrin saturation (TS), and serum ferritin ( S F ) in hemodialysis patients treated with a constant dose of erythropoietin (EPO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
0
9
0
3
Order By: Relevance
“…Also in pre-dialysis patients, and in patients on HD, therapy with iron dextran was able to increase Hb and ferritin levels [13,14,15]. The efficacy and benefit of iron dextran therapy in dialysis patients is also proven in patients with functional or absolute iron deficiency, and with different dosing patterns [16,17,18,19]. …”
Section: Discussionmentioning
confidence: 99%
“…Also in pre-dialysis patients, and in patients on HD, therapy with iron dextran was able to increase Hb and ferritin levels [13,14,15]. The efficacy and benefit of iron dextran therapy in dialysis patients is also proven in patients with functional or absolute iron deficiency, and with different dosing patterns [16,17,18,19]. …”
Section: Discussionmentioning
confidence: 99%
“…82 The diagnostic value of serum ferritin, however, is limited by its behavior as a potent acute phase reactant. [118][119][120] Given the low sensitivity, a high or normal serum ferritin is not sufficient to exclude the possibility of iron deficiency. [118][119][120] Given the low sensitivity, a high or normal serum ferritin is not sufficient to exclude the possibility of iron deficiency.…”
Section: Monitoring a And D Diagnosis O Of I Iron D Deficiency In C Cmentioning
confidence: 99%
“…[118][119][120] As a result, low values of transferrin saturation cannot reliably make the diagnosis of iron deficiency in this patient population, and results are often falsely positive. K/DOQI™ guidelines recommend using a value of less than 20% as an indicator of iron deficiency in patients with CKD.…”
Section: Monitoring a And D Diagnosis O Of I Iron D Deficiency In C Cmentioning
confidence: 99%
“…Ferritin correlates well with iron stores in patients with or without ESRD. 15,40,41 In lieu of transferrin, the per centage of hypochromic RBCs greater than 5-10% can be used. 14,21,33 Two studies 42,43 suggested that ferritin is a use ful marker in cancer patients not receiving chemotherapy, but is not as plausible in those receiving chemotherapy.…”
Section: Iron Deficiency and Supplementationmentioning
confidence: 99%